A wireless reconfigurable modular manipulator and its control system. (February 2021) - Xu, Wenfu; Han, Liang; Wang, Xin; Yuan, Han
Abstract: As the core of Industry 4.0, the intelligent manufacturing technology requires robotic arms to be networked, customized and flexible. Traditional industrial robots have a large number of electrical cables. The end effectors cannot be easily replaced. In this paper, a reconfigurable modular arm with quick replacement of tools and its neural adaptive control system are developed. It consists of an anthropomorphic 7 degree-of-freedom (DOF) manipulator, a reconfigurable connection mechanism (RCM) and a wireless controller. Based on the modular design ideas, each joint is integrated with a motor, a harmonic reducer, two encoders and a servo controller to achieve high torque capacity but keep light weight. Shape Memory Alloy (SMA) wires and steel spheres are used in the RCM to provide mechanical and electrical connections between the arm and the end effector for rapid replacement. The central controller communicates with each servo controller through wireless communication links. Furthermore, the neural adaptive control method compensating position and force tracking errors caused by the model uncertainty and time delay is addressed. Finally, the prototype is fabricated and experiments are carried out. The developed arm has high position accuracy, force control accuracy, and reliable reconfigurable capability. Highlights: The new reconfigurable connection mechanism (RCM) of the arm is developed. The tools of the arm can be quickly replaced. The wireless controller which replaced the communication cables is developed. The neural adaptive control is developed to handle uncertain models and time delay.